A methodology for quantifying global consumptive water use of coffee for sustainable production under conditions of climate change - Eriyagama, Nishadi; Chemin, Yann H.; Alankara, Ranjith (2013)
Coffee is the second most traded commodity in the world after oil. A sustainable coffee industry is crucial to maintaining global agriculture, trade, human and environmental well-being, and livelihoods. With increasing water scarcity and a changing climate, understanding and quantifying the risks associated with water, a primary input in coffee production, is vital. This methodological paper examines the means of quantifying: (a) 'current' consumptive water use (CWU) of green coffee (coffee beans at harvest time) globally; (b) coffee 'hot spots' and 'bright spots' with respect to levels of CWU, yields and water stress; and (c) possible impacts of climate change on the CWU of coffee. The methodology employs satellite-derived monthly evapotranspiration data, and climate projections from two global circulation models for three future scenarios. Initial estimates suggest that currently (on average) 18.9 m3/kg of water is consumed in producing one unit of green coffee. The same estimate for irrigated coffee is 8.6 m3/kg, while that for rain fed coffee is 19.6 m3/kg. Climate scenarios show that effective mean annual rainfall in many major coffee areas may decrease by the 2050s. The generic methodology presented here may be applied to other crops, too, if crop data are available.